The Meaning of Social Criticism in the Song Fragile (玻璃心/ Bōlíxīn) Namewee ft. Kimberley Chen: Critical Discourse Analysis of Van Dijk - Muslimat, Andi Filsah; Halidun, Wa Ode Siti Hardianti (Universitas Negeri Semarang, 2025)
This research aims to determine the discourse structure (text), social cognition, and social context in the song Fragile